The Effect of Alkali Pretreatment and Different Parts of Sargassum polycystum Thallus on Alginic Acid Attributes - Sumandiarsa, IKetut; Santoso, Joko; Priasmoro, Ghifari Pandu; Uju, Uju; Subaryono, Subaryono (:Agency for Marine and Fisheries Research and Human Resources, Indonesia, 2024)
Alginic acid is an intermediate product in the alginate extraction process. In this study, alginic acid was generated from three separate sections of the thallus. The study aimed to define the influence of alkali solvents for pretreatment and the thallus parts from S. polycystum to produce alginate. Thus, this study identifies the proper utilization of seaweed as a source of alginate. The extraction procedure to obtain alginic acid was performed using Na2CO3 at a 2% concentration. The pretreatment improved the quality before extraction by soaking in KOH as a solvent. The statistical analysis was used to define significant differences in the pretreatment and thallus parts of the S. polycystum using ANOVA and the Tukey test as the post hoc. Alkali pretreatment and thallus sections substantially influence alginic acid yield, viscosity, and gel strength. Yield, ash content, moisture, pH, viscosity, whiteness degree, and gel strength of the best alginic acid chosen (pretreatment with KOH 0.90% from the basal section) were around 21.51 %, 10.34 %, 7.04 %, 2.54, 53.37 cP, 57.91 %, and 58.80 g/cm2, respectively. Except for the ash content parameter, the qualities of the alginic acid generated satisfied the standard. In conclusion, it is a better understanding of the alginate production from different thallus parts, making utilization more effective.